Loss-of-function variants in SRRM2 cause a neurodevelopmental disorder - Cuinat, Silvestre; Nizon, Mathilde; Isidor, Bertrand; Stegmann, Alexander; van Jaarsveld, Richard H.; van Gassen, Koen L.; van der Smagt, Jasper J.; Volker-Touw, Catharina M.L.; Holwerda, Sjoerd J.B.; Terhal, Paulien A.; Schuhmann, Sarah; Vasileiou, Georgia; et al. (Genetics in Medicine, 2022)
Purpose: SRRM2 encodes the SRm300 protein, a splicing factor of the SR-related protein family characterized by its serine- and arginine-enriched domains. It promotes interactions between messenger RNA and the spliceosome catalytic machinery. This gene, predicted to be highly intolerant to loss of function (LoF) and very conserved through evolution, has not been previously reported in constitutive human disease. Methods: Among the 1000 probands studied with developmental delay and intellectual disability in our database, we found 2 patients with de novo LoF variants in SRRM2. Additional families were identified through GeneMatcher. Results: Here, we report on 22 patients with LoF variants in SRRM2 and provide a description of the phenotype. Molecular analysis identified 12 frameshift variants, 8 nonsense variants, and 2 microdeletions of 66 kb and 270 kb. The patients presented with a mild developmental delay, predominant speech delay, autistic or attention-deficit/hyperactivity disorder features, overfriendliness, generalized hypotonia, overweight, and dysmorphic facial features. Intellectual disability was variable and mild when present. Conclusion: We established SRRM2 as a gene responsible for a rare neurodevelopmental disease.
CRIS-Team Scopus Importer:2022-06-03
Keywords: Intellectual disability; Molecular genetics; Neurodevelopment; Spliceosome; SRRM2